Development economics theory, empirical research, and policy analysis - Schaffner, Julie (Hoboken, NJ John Wiley & Sons, Inc., 2014)
Development Economics: Theory Empirical Research and Policy Analysis by Julie Schaffner offers a means to think about development and policy in a way that is disciplined by economic theory and informed by empirical research. The main goal of this text is to get readers to think rigorously using tools of economic analysis. This text will help to define development objectives, understand the development process, identify potential barriers to development, design candidate development interventions, and analyze the multidimensional impact of theory, empirical research and policy analysis within the study of economic development--Provided by publisher.
Contents: PART I: Introduction - What is Development Economics Good for? - - PART II: Development Objectives and the Big Picture - Well Being - - Economic Growth - - Economic Growth Theory in Historical Perspective - - Poverty, Inequality, and Vulnerability - - PART III: Analytical Framework: Decisions, Markets, and Intstitutions - Consumption, Time Allocation, and Production Choices - - Households - - Domestic Markets for Goods and Services - - Labor Markets - - investment and Financial Markets - - International Markets and General Equilibrium - - Institutions and Cooperation - - Policy, Governance, and Political Economy - - PART IV: Policy Analysis Approach and Applications - Policy Analysis - - Targeted Transfer Programs - - Workfare - - Agricultural Market Interventions and Reforms - - Infrastructure Policies and Programs - - Education - - Agricultural Research and Extension - - Microfinance - - Public Health, Health Care, and Health Insurance.
Includes index.
Keywords: Economic development; Economic policy